Nepal Human Development Note : Access, Equity, and Quality in the Education, Health and Social Protection Sectors - World Bank (Washington, DC, 2015)
Investments in education, health and social protection are the key to improving the state of human development in any society. In recent years, Nepal too has invested heavily in these sectors, particularly in education and health. This note provides an overview of the progress and current state of access and equity in these three sectors. It also presents evidence on some aspects of quality in the education and social protection sectors. While the country has made substantial improvements in different indicators of access at the aggregate level, disaggregated data show that disparities in access continue to exist across demographic and geographical dimensions. There is some evidence of improvement in the quality of educational inputs over the years, but the quality of outcomes remains poor.